2010
DOI: 10.1038/cdd.2010.125
|View full text |Cite
|
Sign up to set email alerts
|

The DNA repair complex Ku70/86 modulates Apaf1 expression upon DNA damage

Abstract: Apaf1 is a key regulator of the mitochondrial intrinsic pathway of apoptosis, as it activates executioner caspases by forming the apoptotic machinery apoptosome. Its genetic regulation and its post-translational modification are crucial under the various conditions where apoptosis occurs. Here we describe Ku70/86, a mediator of non-homologous end-joining pathway of DNA repair, as a novel regulator of Apaf1 transcription. Through analysing different Apaf1 promoter mutants, we identified an element repressing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…Apoptotic protease activating factor 1 (APAF1) is a crucial component of the apoptosome that is present in humans and mice (24,25) and is assembled in response to cellular stress, including DNA damage, hypoxia and oncogene activation (2628). APAF1 is closely related to several oncogenes and tumor suppressor genes, including B-cell lymphoma-2 (Bcl-2) and p53 (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic protease activating factor 1 (APAF1) is a crucial component of the apoptosome that is present in humans and mice (24,25) and is assembled in response to cellular stress, including DNA damage, hypoxia and oncogene activation (2628). APAF1 is closely related to several oncogenes and tumor suppressor genes, including B-cell lymphoma-2 (Bcl-2) and p53 (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…3). It has been shown that Ku can regulate the expression of Apaf1, a pro-apoptotic protein which is fundamental for the execution of the mitochondrial apoptotic pathway (26). Ku-mediated Apaf1 regulation is dynamically modulated on DNA damage: As soon as DNA is damaged, Ku protects cells from apoptosis by blocking Apaf1 transcription; when the DNA damage accumulates highly inside the cells, Ku leaves the Apaf1 promoter, thereby contributing both to the up-regulation of its expression and to the occurrence of apoptosis.…”
Section: Kumentioning
confidence: 99%
“…Both epigenetic and transcriptional factor-mediated regulation of Apaf-1 and PC-9 expression levels plays an important role in predisposition of cells to activate the apoptosome apparatus (4)(5)(6)(7)(8). However, the processes of apoptosome assembly and functioning in cancer cells are under a variety of negative and positive modes of post-translational regulation (9,10).…”
Section: Introductionmentioning
confidence: 99%